The Shoes of the Fisherman - Anderson, Michael (Warner Home Video, 2003)
Anthony Quinn and Sir Laurence Olivier head a distinguished international cast in this passionate, visionary drama about the election of the first Russian Pope and its effect on the world peace. Michael Anderson (Around The World in 80 Days) directs this stirring rendition of Morris. L. West's best seller in a way that "makes the spectacles vividly convincing... and he is even better with his intimate scenes" (New York Post). Out of a half-century career of great portrayals, Quinn makes Pope Kiril I one of his most memorable. Sir John Gielgud is the Vicar preceeding Quinn and Vittorio De Sica, Oskar Werner and Leo McKern (National board of Review Award winner as Best Supporting Actor) offer stellar support as members of the Vatican's inner circle. With the powerful image of a world on the brink of self-destruction, this inspiring epic remains as timely as ever. Movingly scored by veteran Alex North (An Academy Award nominee and a Golden Globe winner for his work), The Shoes of the Fisherman is a "transcedent film" (Gene Shalit, Look)